Cumulative Effect of pH and Redox Triggers on Highly Adaptive Transient Coacervates. Issue 24 (20th March 2023) - Chowdhuri, Sumit; Das, Saurav; Kushwaha, Ritvika; Das, Tanushree; Das, Basab Kanti; Das, Debapratim
Abstract: An intricate synergism between multiple biochemical processes and physical conditions determines the formation and function of various biological self‐assemblies. Thus, a complex set of variables dictate the far‐from‐equilibrium nature of these biological assemblies. Mimicking such systems synthetically is a challenging task. We report multi‐stimuli responsive transient coacervation of an aldehyde‐appended polymer and a short peptide. The coacervates are formed by the disulphide linkages between the peptide molecules and the imine bond between the polymer and the peptide. Imines are susceptible to pH changes and the disulphide bonds can be tuned by oxidation/reduction processes. Thus, the coacervation is operational only under the combined effect of appropriate pH and oxidative conditions. Taking advantage of these facts, the coacervates are transiently formed under a pH cycle (urea‐urease/gluconolactone) and a non‐equilibrium redox cycle (TCEP/H2 O2 ). Importantly, the system showed high adaptability toward environmental changes. The transient existence of the coacervates can be generated without any apparent change in size and shape within the same system through the sequential application of the above‐mentioned nonequilibrium reaction cycles. Additionally, the coacervation allows for efficient encapsulation/stabilisation of proteins. Thus, the system has the potential to be used for protein/drug delivery purposes in the future. Abstract : Multimodal transience . A highly adaptive coacervate is reported that can be formed transiently under the influence of two different triggers, pH and redox. The cumulative effect of both triggers results in the coacervation and the transient cycles can be operated sequentially for multiple cycles.